2016
DOI: 10.1007/s12282-016-0742-z
|View full text |Cite
|
Sign up to set email alerts
|

Overcalling low-risk findings: grouped amorphous calcifications found at screening mammography associated with minimal cancer risk

Abstract: Grouped amorphous calcifications identified on screening mammography contribute minimally to detection of breast cancer and are not thought to be associated with any identifiable improvement in prognosis; present recommendations concerning this finding may result in false positives and overdiagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 10 publications
1
14
0
9
Order By: Relevance
“…In a recent study, Iwase et al (8) showed only six of 216 (2.8%) grouped amorphous calcifications were malignant and suggested that biopsy of such calcifications would increase the number of false-positive findings. We found a higher malignancy rate for grouped amorphous calcifications (25 of 356 [7.0%]), which is similar to the findings of a recent study by Kim et al (9), who found seven of 92 grouped amorphous calcifications (7.6%) were malignant (9).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Iwase et al (8) showed only six of 216 (2.8%) grouped amorphous calcifications were malignant and suggested that biopsy of such calcifications would increase the number of false-positive findings. We found a higher malignancy rate for grouped amorphous calcifications (25 of 356 [7.0%]), which is similar to the findings of a recent study by Kim et al (9), who found seven of 92 grouped amorphous calcifications (7.6%) were malignant (9).…”
Section: Discussionmentioning
confidence: 99%
“…2 Amorphous was one of the suspicious morphologies of calcifications categorized by the 5th edition of the Breast Imaging Reporting and Data System (BI-RADS), defined as relatively small and fuzzy calcifications with diameters less than 0.5 mm and was recommended as category 4B with a positive predictive value (PPV) of approximately 20%. 3 Currently, several studies [4][5][6][7] have suggested that not all amorphous calcifications require a biopsy. Especially for grouped amorphous calcifications found by screening mammograms, biopsy may lead to false positives and overdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…False-positive results and unnecessary recalls or biopsies are considerable disadvantages of screening. The appropriate application of BI-RADS category 4 and its subdivision, which account for the majority of tissue diagnosis recommendations, is a crucial aspect of addressing these concerns (6,7). Unfortunately, category 4 subdivisions are infrequently utilized (33%) and used even less for calcifications than for architectural distortion or asymmetry (7).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies revealed the lowest PPV of amorphous calcification to range from 7.2% to 10.5%, even within the range of category 4A (2,3,9). To stratify its likelihood of malignancy and reduce unnecessary biopsies, 'grouped' amorphous calcification was investigated and lowered all PPVs, which ranged from 2.8% to 7.6%, corresponding to category 3 or 4A (2,3,6,9). In our study, however, coarse heterogeneous morphology had a lower PPV (11.1%) than amorphous morphology (13.0%) (Table 1), and 'grouped' coarse heterogeneous calcification had much lower PPV (7%) than 'grouped' amorphous calcification (16%).…”
Section: Discussionmentioning
confidence: 99%